Étude contrastive du système des pronoms en français et en roumain (du point de vue du système linguistique et du point de vue socioculturel) - Bălăcescu, Ioana Adriana (Wydawnictwo Naukowe UAM, 2000)
With regard to the use of pronouns Romanian shares a number of features with other Romance languages in opposition to French and English, due to the linguistic system: the pronouns are not obligatory because of the morphological markedness o f the verbal forms. For reasons linked to the socio-cultural system however the use of pronouns is far more differentiated in Romanian than in any other Romance or Anglo- Saxon language.
Comparative analysis of the system of prepositions in French and Romanian. From the point of view of the linguistic system and from the sociocultural point of view